DAMPAK GUNA LAHAN TERHADAP TINGKAT KEMAMPUAN KINERJA JALAN STUDI KASUS : JALAN AHMAD YANI DI KECAMATAN KARTASURA - Taufik Setyawan; Mila Karmilah (Jurnal Planologi, 2017)
The use of land as a trade and service area contributes greatly to the development of urban economic structures, including in the District of Kartasura. Especially Kartasura's market activity which is always developing because it is a place to fulfill primary needs. However, the existence of this market and also the trade and service activities around it are increasingly troubling due to irregularities and disrupting transportation activities around the market. Geographically, Kartasura Subdistrict is quite close to the Surakarta City area (around 10 Km), and Surakarta City has a very rapid and dense development intensity and has a limited development area, so the development of socio-economic activities tends to move towards the Kartasura Sub-District area.Close socio-economic relations with Surakarta City made Kartasura experience rapid development in the growth of new activities along the A. Yani road. Such as education, health, trade and services, industry and office activities. With the growth of new activities along the A Yani road, traffic jams often occur at peak hours. The congestion is due to the mixture between modes of transportation, trade, industry and offices.The purpose of this study is to identify the performance of the A Yani road, to determine the effect of land use on congestion that occurs. To achieve these objectives, the analysis used is quantitative calculations. By comparing the road conditions at peak and non peak hours on the A Yani road. The method used in this study is analyzing the volume of the road (V) A Yani experiencing congestion, analyzing side barriers, speed, road capacity (C) A Yani, and the level of road service (V / C) A Yani. In addition to the quantitative analysis also conduct qualitative analysis to clarify the quantitative analysis that has been done. So that what is a problem on Jalan A Yani can also be analyzed, what are the factors that cause congestion and finally show conclusions and recommendations of problems.Keywords: Land use, Traffic Congestion